Science sans conscience : la satire de la science dans l’œuvre de Jonathan Swift - Nathalie Zimpfer (Etudes Epistémè)
Satire on science has often been regarded by critics as a marginal aspect of Jonathan Swift’s work. Yet it is part and parcel of a battle that the author of Gulliver’s Travels indefatigably fought against the "Moderns." Swift’s satire on science should not however be considered as merely symptomatic of a larger endeavour. Its originality and specifity lie in its rhetoric, which also betrays the evolution of Swift’s approach from a rather localized satire to a more radical critique.